The figure of Amir Temur in the literatures of Europe - Shirin Hikmatovna, Qurbonova; Komila Hasanovna, Sayitova; Shahlo Maqsudovna, Tillayeva; Nasiba Orzuyevna, Abdullayeva (International Journal of Psychosocial Rehabilitation, 2020)
The article analyzes the figure of the great warrior A.Temur in the literatures of Europe, describing the perfect character and personality, formally assuming the title Sahib Qiran-I Soniy (the second Lord of the Fortunate Conjunction)